The X of de X Generation (XXI Century. Spanish Literature and Culture, 2004)
The excuses of intellectual shallowness, fake orthodoxy, playing the victim and violence,heterodoxy, ecstasy- literal and metaphorical- of the age in which one lives… these are all the unknownsthat play a part in the task of clearing the X of the so called ‘generation X’, whose result is the assumptionthat it is a group of young narrators who take advantage of the violent, aggressive and rough part oflanguage to express themselves.
Keywords: Novel; Narrative; aggressive language; Generation x